Self Expression Art Education Orientation : Art Education for Early Childhood in the Independent Learning Curriculum - Fifiet Dwi Tresna Santana; Hartono Hartono; Tati Narawati; Agus Cahyono; Rivaldi Indra Hapidzin (International Conference on Science, Education, and Technology, 2022)
Abstrak. The emergency curriculum is a designation that is in accordance with the conditions during the covid-19 pandemic. This curriculum is a simplified curriculum from the 2013 curriculum. The independent learning curriculum provides space for education, especially early childhood education . The purpose of this paper is that this curriculum creates character education by building local wisdom and the uniqueness of each in their learning. In addition, this curriculum supports the government's efforts to restore learning through character planting in self-expression art education orientation . Art education in PAUD should be a means of training the skills and coordination of children's movements as well as a means to introduce and instill the value of Indonesian art and culture. This research is a literature review type, in this case the researcher analyzes the emergency curriculum for arts education in PAUD. For this reason, the results of this paper assume that the art of dance in PAUD is as an implementation of the prototype curriculum/independence to learn PAUD and self-expression art education in strengthening children's character planting, namely with creative dance children can grow creative, independent and critical reasoning and the principle is a student centered approach.